AHR2 mediates cardiac teratogenesis of polycyclic aromatic hydrocarbons and PCB-126 in Atlantic killifish (Fundulus heteroclitus) - Clark, Bryan W. (2010)
Exposure of developing fish to polycyclic aromatic hydrocarbons (PAHs) and halogenated aromatic hydrocarbons (HAHs) results in a suite of defects including cardiac malformation, pericardial and yolk sac edema, craniofacial defects, and hemorrhaging. Several populations of Atlantic killifish or mummichog (Fundulus heteroclitus) on the Atlantic coast of the United States are resistant to the developmental and acute toxicity caused by PAHs and HAHs; this has made Fundulus a valuable model for studying aryl hydrocarbon sensitivity and adaptation. In order to further increase the utility of Fundulus, better understanding of the components of the molecular pathways governing aryl hydrocarbon response in Fundulus is required. The aryl hydrocarbon receptor (AHR) is known to mediate many of the toxic responses to PAHs and HAHs. A single AHR has been identified in mammals, but Fundulus has two AHRs and their relative roles are not clear. In the current study, translation-blocking and splice-junction morpholino gene knockdown was used to determine the roles of AHR1 and AHR2 in mediating cardiac teratogenesis induced by β-naphthoflavone (BNF), benzo[k]fluoranthene (BkF), and 3, 3′, 4, 4′, 5-pentachlorobiphenyl (PCB-126). Here we report that AHR2 and not AHR1 knockdown resulted in rescue of teratogenicity induced by BNF, BkF, and PCB-126. These data demonstrate that AHR2 is the primary mediator of cardiac teratogenesis caused by multiple aryl hydrocarbons in Fundulus and suggest that suppression of the AHR pathway through modulation of AHR2 is a plausible mechanism for PAH resistance in adapted fish. Additionally, this is the first reported use of splice-junction morpholinos in Fundulus.